Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.12669/pjms.344.15296
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two types of exercises in the treatment of lumbar spinal stenosis

Abstract: Objective:To evaluate the efficacy of core stability exercise versus conventional exercise in the treatment of lumbar spinal stenosis.Methods:Between January 2014 and May 2017, patients with lumbar spinal stenosis were recruited and divided into group of core stability exercise or conventional exercise randomly. All the patients were treated using middle frequency electrotherapy, in addition to that, the patients in group of core stability exercise were treated using core stability exercise. The patients in gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Participant characteristics, interventions and comparators, follow-up time points, risk of bias, and intervention reporting quality of the included trials are presented in Table 2. Ten trials [25][26][27][28][29][30][31][32][33][34][35] had two treatment arms, and the remainder had three arms. [36][37][38] The included trials involved a total of 1440 participants with a mean age of 65 years (standard deviation 9), of whom 985 were allocated to a supervised or structured home exercise intervention.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Participant characteristics, interventions and comparators, follow-up time points, risk of bias, and intervention reporting quality of the included trials are presented in Table 2. Ten trials [25][26][27][28][29][30][31][32][33][34][35] had two treatment arms, and the remainder had three arms. [36][37][38] The included trials involved a total of 1440 participants with a mean age of 65 years (standard deviation 9), of whom 985 were allocated to a supervised or structured home exercise intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Over half of the exercise interventions (15/23) were 'multi-modal' in nature, combined with manual therapy, passive modalities, medical treatments, education, or psychologically informed approaches. Studies published in the last 5 years [29][30][31][32][33][34][35]37 were less likely to include passive modalities and more likely to include a psychologically informed approach.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kim et al [33] found that after 4 weeks of lumbar dorsiflexion training in 15 patients with LSS, the mean scores on the Oswestry Disability Index (ODI), Spinal Stenosis Scale, and Roland-Morris Disability Questionnaire decreased by >25%, indicating that the patients' pain and lower limb function were obviously improved. Mu et al [34] found that Japanese Orthopaedic Association scores and walking distance were improved in patients with LSS after core strength training such as plank, side plank, and bridge. Pauwels et al [35] instructed 12 patients with LSS to perform bicycling, and 7 of them showed a mean decrease of 63.5% in the numerical rating scale after 3 months, suggesting marked relief of neurogenic pain.…”
Section: Anti-mechanical Stresses Treatment Of Lssmentioning
confidence: 99%